2012
DOI: 10.1371/journal.pone.0033514
|View full text |Cite
|
Sign up to set email alerts
|

RpoS Regulates a Novel Type of Plasmid DNA Transfer in Escherichia coli

Abstract: Spontaneous plasmid transformation of Escherichia coli is independent of the DNA uptake machinery for single-stranded DNA (ssDNA) entry. The one-hit kinetic pattern of plasmid transformation indicates that double-stranded DNA (dsDNA) enters E. coli cells on agar plates. However, DNA uptake and transformation regulation remain unclear in this new type of plasmid transformation. In this study, we developed our previous plasmid transformation system and induced compet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 40 publications
0
33
1
Order By: Relevance
“…Furthermore, we found that DNA uptake gene orthologs required for other naturally transformable species were not involved in this transformation system (9), which implied that a different molecular mechanism of competence development and DNA uptake was being used. As reported by our group and others, the general stress response regulator RpoS ( S ) was shown to mediate natural transformation (10), and transformation frequencies were apparently increased when rpoS was induced in the liquid culture stage but did not change significantly when rpoS was induced on solid medium (11). Moreover, OmpA, a membrane protein, has been reported to block DNA transfer, and the null mutation leads to a boost in transformation on agar plates (12).…”
mentioning
confidence: 55%
“…Furthermore, we found that DNA uptake gene orthologs required for other naturally transformable species were not involved in this transformation system (9), which implied that a different molecular mechanism of competence development and DNA uptake was being used. As reported by our group and others, the general stress response regulator RpoS ( S ) was shown to mediate natural transformation (10), and transformation frequencies were apparently increased when rpoS was induced in the liquid culture stage but did not change significantly when rpoS was induced on solid medium (11). Moreover, OmpA, a membrane protein, has been reported to block DNA transfer, and the null mutation leads to a boost in transformation on agar plates (12).…”
mentioning
confidence: 55%
“…During transformation of E. coli on plates, OMPs should directly contact with the surface of agar plates where DNA uptake occurs [13]. Our previous work demonstrated that agar significantly promotes transformation on plates [18].…”
Section: Resultsmentioning
confidence: 99%
“…Our previous work showed that natural transformation of E. coli is regulated by the transcription regulator RpoS [13], which is able to compete with σ 70 [33], the principle regulator of ompA (Fig. S2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations